Introduction of «Ukrainization» in the Higher Education System in the USSR of the 1920-s - Mazurenok, Maryna (Pedagogical Discourse, 2013)
The activities of People’s Commissariat of Ukrainian Social Soviet Republic for introduction the policy of «Ukrainization» in higher education in 1920 are highlighted. The legislative base of «Ukrainization» policy is analysed. The features of Ukrainization in educational process in the USSR’s higher educational establishments are observed. Attention is paid to the objective and subjective factors of slow introduction of ukrainization in higher education. The impact of government policy on the development of the higher education system in USSR is investigated.